HUBUNGAN PDRB SEKTOR PERTANIAN DENGAN JUMLAH PENDUDUK MISKIN DI KABUPATEN MINAHASA (Agricultural Sector GRDP Relations With The Number Of Poor Populations In Minahasa Regency) - Vonita Silvia Taula; Theodora M. Katiandagho; Oktavianus Porajouw (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2022)
Minahasa Regency is one of the regencies in North Sulawesi Province which relies on the agricultural sector as a support for the existing community's economy. Minahasa Regency has considerable potential in the agricultural sector because it is supported by relatively good land and climate conditions, but the poverty rate in Minahasa Regency is still relatively high. The objective of this research is to determine the relationship between GRDP in the agricultural sector and the number of poor people in Minahasa Regency. The time of this research was carried out from January to March 2021. The data variables used in this study were the GRDP of the Agricultural Sector and the Number of Poor Population in Minahasa Regency which were secondary data for the period 2008 to 2019 from the Central Bureau of Statistics of North Sulawesi. The data analysis method used is correlation analysis. The research results showed that there was a negative relationship between the GRDP of the agricultural sector and the number of poor people, namely the correlation value of -0.116, which means that when there is an increase in GRDP in the agricultural sector, the number of poor people will decrease.